Development of risk-based inspection of 28-years-old subsea sales gas pipelines to support the energy demand - Soedarsono, Johny; Wijaya, Arie; Aditiyawarman, Taufik; Kaban, Agus; Riastuti, Rini; Ramdhani, Rizal Tresna; Ayende (Eastern-European Journal of Enterprise Technologies, 2023)
In the oil and gas industry, maintaining the integrity of production equipment is critical to ensuring the industry’s sustainability. Failure to maintain the integrity of production equipment can result in financial losses for the business. The management of production equipment nearing the end of its design life faces an increasing cost of Inspection, Maintenance, and Repair (IMR). As a result, a strategy to improve the efficiency of IMR is essential. Recent IMR management practices include predictive Risk-Based Inspection (RBI), which is more efficient than Time-Based Inspection (TBI). The research intends to evaluate the 28-year-old subsea sales gas pipeline using API 581 standard quantitative methodology by utilizing the Inline Inspection (ILI). Specifically, the study focuses on measuring the Probability and Consequence Failure of inspected pipelines. The inspection interval is determined based on the minimum allowable thickness. The risk calculation indicates that 12 pipeline segments are at a medium risk level (3 segments, 1D and 1E, and 2C). The remaining nine segments remain at lower risk (1C). Based on the result, segment nine is accepted as the highest PoF value of 1.04E-4 failures per year due to high depletion values due to the higher CoF value at the leak location. The calculation of the inspection interval indicates that the forthcoming Inspection will be due 20 years post the previous assessment. Another method using the Estimated Repair Factor (ERF) thickness limit approach produces the same results. However, assessment using ASME B31.8S provides different results of 10 years intervals when using the same ILI inspection method. This work can be used as a standard guideline to assess the risk of pipelines over a decade in service